A Case Study of Near-Field Vibration Monitoring, Analysis, And Modeling - Ruilin Yang; James Gunderson; Tamara Whitaker (International Society of Explosives Engineers, 2008)
This paper presents the results of a vibration control project conducted in soft overburden at a surface coal mine located in the western United States. The study uses near-field blast vibration monitoring, analysis and modeling techniques developed in house. Accelerometer-equipped seismographs were utilized for near-field vibration monitoring and analysis. Vibration control was achieved through field data regression as well as vibration modeling using the multiple seed near-field blast vibration model (Yang and Scovira, 2007). The regression was conducted between peak particle vibration parameters and the minimum scaled distance per delay. From the regression analysis, the curves of upper bounds for peak particle vibration parameters and charge weight were developed. The dominant frequencies of the blast vibration were also addressed in this project. The regression curves and near-field vibration model guided the blast design to control blast vibration for maximizing the recovery of coal and maintaining mine productivity.